Diurnal fluctuations in the content of soluble sugars and the expression of the TAI and LIN6 invertase genes and the STP1 sugar transporter gene in the leaves of the tomato (Solanum lycopersicum L.) - M. A. Filyushin; A. V. Shchennikova; E. Z. Kochieva (Вавиловский журнал генетики и селекции, 2025)
The content of hexoses (fructose, glucose) essential for the fruit of the tomato (Solanum lycopersicum L.) is regulated by the joint activity of sucrose hydrolysis enzymes (including invertases), invertase inhibitors, and sugar transporters. In addition to fruit taste, soluble sugars are closely related to the stress resistance of the tomato plant. In this work, we determined the diurnal dynamics of the content of soluble sugars (sucrose, fructose and glucose) and the expression of genes for sucrose hydrolysis enzymes (vacuolar invertase TAI, cell wall invertase LIN6) and the hexose transporter (STP1) in the leaves of the tomato variety Korneevsky. It was shown that both the amount of sugars and the level of transcripts of the TAI, LIN6 and STP1 genes depend on the circadian rhythm and correspond to the biological processes occurring in the plant at different periods of the day. The content of sucrose and hexoses changes in a similar way during the day. At the beginning of the light phase, the concentration of sugars is minimal, at the end it has the highest daily values; at the beginning of the dark phase, it shows a residual increase and then decreases towards the end of the phase. In silico analysis of organ-specific expression of TAI, LIN6 and STP1 in S. lycopersicum cv. Micro-Tom showed the presence of mRNA of all three genes in all tissues. The TAI gene was expressed most strongly in ripe fruits, while the level of LIN6 and STP1 transcripts was extremely low. The level of TAI mRNA in the leaves was ~2 times higher than that of LIN6 and ~27 times higher than that of STP1. Analysis using qRT-PCR of the diurnal dynamics of TAI, LIN6 and STP1 expression in the cv. Korneevsky leaves showed that all three genes were expressed at all points analyzed. Fluctuations in their expression levels occur in a similar manner: mRNA levels reach peak values in the middle of the light and dark phases. The results obtained are important for understanding the functions of invertases and sugar transporters in the tomato plant, and can be used in predicting the stress resistance of plants in tomato breeding.